2014
DOI: 10.1016/j.nedt.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationships between student approaches to learning and group work

Abstract: Keywords:Nursing education Group work First-year experience Student approaches to learning Background and Aim: As part of the process of nursing students becoming 'work ready' within future health care teams, students need the skills to work collaboratively. In higher education, establishing group work assignments is a teaching method to develop group work skills. Not only is group work an important teaching method to develop effective group work skills but it is also used to activate deep learning. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 48 publications
4
39
0
2
Order By: Relevance
“…Several studies have proposed that higher student age is associated with a more productive (e.g., less surface and syllabus-bound) approach to studying (Baeten et al, 2010;Beccaria et al, 2014;Richardson, 2005;Salamonson et al, 2013;Wickramasinghe & Samarasekera, 2011). In the present study, a statistically significant age difference between the cohorts was found, with the third-year students having a higher mean age than the first-year students.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Several studies have proposed that higher student age is associated with a more productive (e.g., less surface and syllabus-bound) approach to studying (Baeten et al, 2010;Beccaria et al, 2014;Richardson, 2005;Salamonson et al, 2013;Wickramasinghe & Samarasekera, 2011). In the present study, a statistically significant age difference between the cohorts was found, with the third-year students having a higher mean age than the first-year students.…”
Section: Discussionsupporting
confidence: 47%
“…In fact, several studies have provided evidence of older students being associated with a more productive (i.e., higher deep/strategic, lower surface) approach to studying when compared to younger students (Baeten et al, 2010;Beccaria, Kek, Huijser, Rose, & Kimmins, 2014;Richardson, 2005;Salamonson et al, 2013;Wickramasinghe & Samarasekera, 2011).…”
mentioning
confidence: 99%
“…approach or another is overly simplistic (Entwistle, 2007), as is inferring that one approach is uniformly better than others (Beattie, Collins, & McInnes, 1997). Approaches to studying have been linked with age and experience (Beccaria, Kek, Huijser, Rose, & Kimmins, 2014;Zeegers, 2001) and with relatively stable personal traits like self-efficacy Prat-Sala & Redford, 2010). Nonetheless, a range of research studies have also found study approaches to be related to aspects of the learning environment (Baeten, Kyndt, Struyven, & Dochy, 2010;Kreber, 2003;Lizzio, Wilson, & Simons, 2002;Richardson, 2010;Sadlo & Richardson, 2003;Trigwell, Prosser, & Waterhouse, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…They repeat Pollack's proposition [35] that undergraduate males may 'present a "mask of bravado or pseudo-resilience' which may project confidence yet hide a troubling sense of isolation". Given the 9:1 ratio of male to female students in every ISO cohort since 2009, it was of special concern that students prone to isolation through lack of social confidence should have the chance of friendship fostered.…”
Section: Fostering Friendshipsmentioning
confidence: 77%